Enzyme replacement therapy in a feline model of Maroteaux-Lamy syndrome. - Crawley, A C (1996)
We report studies that suggest enzyme replacement therapy will result in a significant reduction in disease progression and tissue pathology in patients with Maroteaux-Lamy syndrome (Mucopolysaccharidosis type VI, MPS VI). A feline model for MPS VI was used to evaluate tissue distribution and clinical efficacy of three forms of recombinant human N-acetylgalactosamine-4-sulfatase (rh4S, EC 3.1.6.1). Intravenously administered rh4S was rapidly cleared from circulation. The majority of rh4S was distributed to liver, but was also detected in most other tissues. Tissue half-life was approximately 2-4 d. Three MPS VI cats given regular intravenous infusions of rh4S for up to 20 mo showed variable reduction of storage vacuoles in Kupffer cells and connective tissues, however cartilage chondrocytes remained vacuolated. Vertebral bone mineral volume was improved in two MPS VI cats in which therapy was initiated before skeletal maturity, and increased bone volume appeared to correlate with earlier age of onset of therapy. One cat showed greater mobility in response to therapy.